2007
DOI: 10.1111/j.1600-0463.2007.apm_595.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence conservation of subdominant HLA‐A2‐binding CTL epitopes in HIV‐1 clinical isolates and CD8+ T‐lymphocyte cross‐recognition may explain the immune reaction in infected individuals

Abstract: Cytotoxic T-lymphocytes (CTL) are critical for immune control of infection with human immunodeficiency virus type-1 (HIV-1) and searches for relevant CTL epitopes for immune therapy are ongoing. Recently, we identified 28 HLA-A2-binding HIV-1 CTL epitopes (1). In this follow-up study we fully genome sequenced HIV-1 from 11 HLA-A2(+) patients to examine the sequence variation of these natural epitopes and compared them with the patient's CD8(+) T-cell recall response. Often the epitope was conserved but only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Sequencing plasma HIV-1 RNA confirmed that in all individuals the majority of the epitopes or epitope variants previously shown to cross-react in HLA-A Ã 0201 mice [14] were present before immunization (Table 1). We followed plasma HIV-1 viral load and CD4 þ T-cell counts for 1 year prior to and up to 8 months after the dendritic cell immunization (Fig.…”
Section: Effect On Clinical Parameters By Dendritic Cell Immunizationsupporting
confidence: 52%
See 4 more Smart Citations
“…Sequencing plasma HIV-1 RNA confirmed that in all individuals the majority of the epitopes or epitope variants previously shown to cross-react in HLA-A Ã 0201 mice [14] were present before immunization (Table 1). We followed plasma HIV-1 viral load and CD4 þ T-cell counts for 1 year prior to and up to 8 months after the dendritic cell immunization (Fig.…”
Section: Effect On Clinical Parameters By Dendritic Cell Immunizationsupporting
confidence: 52%
“…We tested the immunogenicity of the selected peptides in HLA-A Ã 0201 transgenic mice and confirmed their infrequent targeting but in-vivo processing in untreated HIV-1-infected individuals [13,14]. To compensate for the high diversity of HIV-1 and investigate the potential for targeting the virus at several different highly conserved regions simultaneously [15], we selected seven of these novel HLA-A2 CTL epitopes derived from several proteins in HIV-1 [14,16]. Weak immunogenic target epitopes were modified into potent peptide immunogens by anchor optimization and confirmed improved immunogenicity and cross-reaction to the target epitopes [13,14].…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations